Discourse patterns used by extremist Salafists on Facebook: identifying potential triggers to cognitive biases in radicalized content. Issue 3 (4th May 2022) - Bouko, Catherine; Naderer, Brigitte; Rieger, Diana; Van Ostaeyen, Pieter; Voué, Pierre
ABSTRACT: Understanding how extremist Salafists communicate, and not only what, is key to gaining insights into the ways they construct their social order and use psychological forces to radicalize potential sympathizers on social media. With a view to contributing to the existing body of research which mainly focuses on terrorist organizations, we analyzed accounts that advocate violent jihad without supporting (at least publicly) any terrorist group and hence might be able to reach a large and not yet radicalized audience. We constructed a critical multimodal and multidisciplinary framework of discourse patterns that may work as potential triggers to a selection of key cognitive biases and we applied it to a corpus of Facebook posts published by seven extremist Salafists. Results reveal how these posts are either based on an intense crisis construct (through negative outgroup nomination, intensification and emotion) or on simplistic solutions composed of taken-for-granted statements. Devoid of any grey zone, these posts do not seek to convince the reader; polarization is framed as a presuppositional established reality. These observations reveal that extremist Salafist communication is constructed in a way that may trigger specific cognitive biases, which are discussed in the paper.